Movimentos de preços por faixas de renda: uma nota - Soares, Paulo de Tarso P. L.; Carmo, Heron Carlos E. do; Bueno, Rodrigo De Losso S. (Estudos Econômicos (São Paulo), 1995)
A reworking of the Family Budget Research data, which is utilized to calculate the cost of living index of FIPE, indicates an increasing dispersion of price changes with respect to the different income levels, after the cruzeiro was substituted by the real. This suggests that the price stabilization strategy itself may well be generating significant distributive conflicts. The low levels cinco of quarterly inflation data, therefore, should not be taking as a sigh that the inflationary process is under control.